Persepsi Mahasiswa Universitas Riau Terhadap Organisasi Pemuda Pancasila di Pekanbaru - Citra Mandasari; Mirza Hardian; Sri Erlinda (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
The presence of a social organization is expected to be able to implement an attitude of nationalism in people's lives. The purpose of this study was to determine the perceptions of Riau University students towards the nationalism attitude of the Pemuda Pancasila social organization in the city of Pekanbaru. This research is a quantitative research with a survey method that is descriptive in nature with the population in this study being Riau University students who know and are familiar with the Pancasila Youth social organization whose number is unknown and can be said to be in an infinite category while the sample in the study was 100 students with the lemeshow formula. The data collection instruments in this study were observation, questionnaires, interviews and documentation. The results of this study are that the average value of the alternative proportion of the dominant respondent's answers is 49.13%, where the range in the